Reconstruction of Dalihan Na Tolu in Batak Culture Towards a Practical Theology Relevant to the Task of the Church - Nainggolan, Rahmat Hasudungan; Binur Panjaitan; Arip Surpi Sitompul (International Journal of Educational Research Excellence (IJERE), 2023)
The role of Dalihan na tolu is something that cannot be separated in the life of the Toba Batak indigenous people. In his role with the task of the church, Dalihan na tolu can go hand in hand in proclaiming the truth of God's Word so that customs and Christianity become one and form new habits, new customs, which are based on the love of Christ. The problem that will be discussed is the reconstruction of Dalihan na tolu in Batak culture towards practical theology that is relevant to the task of the church. The approach method used in this research is a qualitative research method, while the research approach used is a qualitative research approach with the technique of "Observation, interviews, documentation, triangulation/combination". The data used are secondary and primary data. The results show that in the life of the Toba Batak indigenous people, the role of Dalihan na tolu greatly enhances the cooperation of the respective roles of the elements of Dalihan na tolu, namely Somba marhula-hula, Manat mardongan tubu, and elek marboru where these elements are very important and should not be forgotten because it has become a furnace or three supporting stones. The customs carried out prioritize worship and adopt the concept of friendship and kinship in Christianity, namely love and sacrifice.